Equilibrium Effects of Payroll Tax Reductions and Optimal Policy Design - Thomas Breda; Luke Haywood; Haomin Wang (Institute of Labor Economics (IZA), 2022)
Recent empirical literature documents that targeted tax reductions or minimum wages can have unintended reallocation and spillover effects on workers not directly targeted by these policies. We quantify these effects using an equilibrium search-and-matching model estimated on French data before a low-wage payroll tax reduction in 1995; the model features heterogeneous workers and firms, labor taxation, and a minimum wage. Based on our model, the tax reduction led to changes in the vacancy distribution such that it becomes harder for workers to move up the job ladder in terms of firm productivity. We refer to this as the negative reallocation effect. The tax reduction also increased labor force participation of low-productivity workers, leading to a negative spillover effect because these workers create congestion in the labor market, lowering the job-finding rate for all workers. Given these unintended effects, low-wage tax reduction should cover jobs in a broad wage range. Finally, we find that the efficiency-maximizing policy mix involves moderately regressive payroll taxation and a low but binding minimum wage.
Keywords: J64; E24; H24; J38; 330; payroll tax; minimum wage; equilibrium job search; worker and firm heterogeneity